2009
DOI: 10.1063/1.3174262
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced complexation of NH3BH3–H2

Abstract: High pressure Raman spectroscopy of NH 3 BH 3 -H 2 mixtures up to 60 GPa reveals unusual pressure-induced complexation and intermolecular interactions. Stretching modes of H 2 in the complex arise at 6.7 and 10 GPa, increasing in frequency with pressure of up to 60 GPa with different pressure coefficients, and at ϳ40 GPa, the lower frequency mode approaches vibron frequency of bulk H 2 . Pressure-induced transformations in pure NH 3 BH 3 studied up to 60 GPa reveal a disorder-order transition at 1 GPa ͑phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 51 publications
5
46
1
Order By: Relevance
“…This latter study seemed to confirm that a higher concentration of H 2 than 1 : 1 is required for the strong weakening of H 2 vibron frequencies since a study of the SiH 4 ÁH 2 mixture showed a strengthening of vibron frequencies with increasing pressure. This contrasted with the vibron pressure dependence reported in inert-gas mixtures with hydrogen 25,26 or other gases mixed with hydrogen 27,28 where hydrogen vibron frequencies increase with pressure below 100 GPa and the mixtures remained insulating.…”
Section: Recent Approaches For Metallization Of Hydrogencontrasting
confidence: 84%
“…This latter study seemed to confirm that a higher concentration of H 2 than 1 : 1 is required for the strong weakening of H 2 vibron frequencies since a study of the SiH 4 ÁH 2 mixture showed a strengthening of vibron frequencies with increasing pressure. This contrasted with the vibron pressure dependence reported in inert-gas mixtures with hydrogen 25,26 or other gases mixed with hydrogen 27,28 where hydrogen vibron frequencies increase with pressure below 100 GPa and the mixtures remained insulating.…”
Section: Recent Approaches For Metallization Of Hydrogencontrasting
confidence: 84%
“…Raman spectra ( Fig. 1) of ammonia borane (25)(26)(27)(28)(29)(30) and lithium amidoborane (31) at ambient condition have been well documented, and the major Raman modes can be described by their molecular nature: N-H stretching, B-H stretching, and B-N stretching modes. In the Raman spectra, B-H stretching modes of lithium amidoborane appear at lower wavenumbers compared with those of ammonia borane ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High-pressure study of molecular crystals can provide unique insight into the intermolecular bonding forces, such as hydrogen bonding and phase stability in hydrogen storage materials and thus provides insight into the improvement of design (22)(23)(24)(25)(26)(27)(28)(29)(30). For instance, Raman spectroscopic study of ammonia borane at high pressure provided insight about its phase transition behavior and the presence of dihydrogen bonding in its structure (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (12) also recently presented experimental evidence that vibrational (vibron) frequencies are lowered at low pressures when hydrogen is added to SiH 4 . The behavior in SiH 4 ðH 2 Þ 2 contrasts with that of other mixtures of simple materials (13)(14)(15)(16) where hydrogen vibron frequencies increase with pressure in the pressure range below 100 GPa and they remain insulating. This observation indicates that the covalent bond in the H 2 molecules can be effectively modified at relatively low pressure with small change in chemical environment [there is only 11 atom percent Si in SiH 4 ðH 2 Þ 2 ], and would perhaps give rise to a unique metal with properties similar to metallic hydrogen.…”
mentioning
confidence: 83%